2021
DOI: 10.3390/molecules26195828
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Structural Grounds for Anomalous Molecular Mobility in Ionic Liquid Glasses

Abstract: Ionic liquid (IL) glasses have recently drawn much interest as unusual media with unique physicochemical properties. In particular, anomalous suppression of molecular mobility in imidazolium IL glasses vs. increasing temperature was evidenced by pulse Electron Paramagnetic Resonance (EPR) spectroscopy. Although such behavior has been proven to originate from dynamics of alkyl chains of IL cations, the role of electron spin relaxation induced by surrounding protons still remains unclear. In this work we synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 80 publications
2
13
0
Order By: Relevance
“…4C) may be related to the glass-like cross-over in confined acetonitrile. Indeed, for bulk molecular glasses such as orthoterphenyl, 43 ethanol, 44 dibutyl phthalate, 45 or ionic liquids, 44,45 a correlation between the glass transition temperature T g and the enhancement of stochastic librations was observed. For confined solvents, the so-called dynamical cross-over is observed for various systems, including water in between GO planes.…”
Section: Discussionmentioning
confidence: 99%
“…4C) may be related to the glass-like cross-over in confined acetonitrile. Indeed, for bulk molecular glasses such as orthoterphenyl, 43 ethanol, 44 dibutyl phthalate, 45 or ionic liquids, 44,45 a correlation between the glass transition temperature T g and the enhancement of stochastic librations was observed. For confined solvents, the so-called dynamical cross-over is observed for various systems, including water in between GO planes.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, we have reliably shown that the dynamics of alkyl chains, included in the IL structure, play a crucial role in the anomaly, which is fundamentally important [41]. Next, the influence of the spin-probe structure was excluded [43], and the anomaly was observed in glasses of other alkyl-chain-containing molecules (ionic liquids, phthalates, alkyl alcohols, and alkyl benzenes), thus making this phenomenon rather ubiquitous [44]. Furthermore, we studied the influence of water content in IL and found self-assembled domains around solutes in binary IL/water mixtures [47].…”
Section: Introductionmentioning
confidence: 91%
“…A recent series of IL studies using pulse electron paramagnetic resonance (EPR) spectroscopy revealed peculiar molecular dynamics in the glassy state near the glass transition temperature (T g ) [39][40][41][42][43][44][45][46]. Such "structural anomaly" was first found in imidazolium-based ILs, and was later observed for other ILs, phthalates, alkyl alcohols, and alkyl benzenes [44].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to characterizing the local rigidity/stiffness/fragility of ILs, the developed methodology also reveals so-called structural anomalies in ILs [29,30,[32][33][34]. In such anomalous temperatures regions near the glass transition, the molecular mobility decreases upon a temperature increase, which opposes general expectation for most media and materials [29,35].…”
Section: Introductionmentioning
confidence: 99%